Tracking moving objects using topographical indexing. (18th October 2013) - Alamri, Sultan; Taniar, David; Safarb, Maytham; Al‐Khalidi, Haidar; Mustafee, Navonil; Bessis, Nik; Barolli, Leonard; Chen, Xiaofeng; Xhafa, Fatos
Summary With the increasing popularity of Global Positioning System (GPS) technologies, many applications have been developed that are able to browse and monitor their GPS tracks on mobile objects. However, a large number of applications focus only on the region (not the exact coordinate location) where mobile objects are located. Not only the exact coordinate locations of moving objects are not needed but also the exact coordinate locations may sometime be distorted because of the inaccuracy of tracking systems. Therefore, in this paper, we propose an efficient data structure index for the moving objects based on their regional location. The topographical outdoor‐tree (TO‐tree) is based on the connectivity (adjacency) between outdoor cells space. The proposed index can support and enable efficient query processing and efficient updates of moving objects in outdoor space cells. The TO‐tree can serve spatial, topological, and adjacency queries. Experiments suggest that the TO‐tree performs efficiently and incurs less update cost while maintaining satisfactory performance. Copyright © 2013 John Wiley & Sons, Ltd.